2020
DOI: 10.1098/rstb.2019.0651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bayesian and numerical optimization-based diet estimation on herbivorous zooplankton

Abstract: Consumer diet estimation with biotracer-based mixing models provides valuable information about trophic interactions and the dynamics of complex ecosystems. Here, we assessed the performance of four Bayesian and three numerical optimization-based diet estimation methods for estimating the diet composition of herbivorous zooplankton using consumer fatty acid (FA) profiles and resource library consisting of the results of homogeneous diet feeding experiments. The method performance was evaluated in terms of abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In our example, there was a small proportion of herring estimated (i.e., 0.009 or 0.9%) which was the smallest proportion of all the sources. Litmanen et al 30 found that both Bayesian and QFASA methods had more problems identifying absent sources for herbivorous zooplankton when the number of absent sources was higher; however, there were exceptions. Although here MixSIAR did produce a small estimate for herring, more systematic testing is needed in order to understand when an absent source can be correctly identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our example, there was a small proportion of herring estimated (i.e., 0.009 or 0.9%) which was the smallest proportion of all the sources. Litmanen et al 30 found that both Bayesian and QFASA methods had more problems identifying absent sources for herbivorous zooplankton when the number of absent sources was higher; however, there were exceptions. Although here MixSIAR did produce a small estimate for herring, more systematic testing is needed in order to understand when an absent source can be correctly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of biological systems, particularly that they are often influenced by multiple factors, it would be advantageous to use modelling approaches that allow for the inclusion of ecological information. MixSIAR models diet proportions as a function of ecologically meaningful factors 11 ; previous knowledge can be incorporated into models as informative priors, as can the uncertainty in source values, unlike QFASA which can use only mean source values 30 . Despite the promise of MixSIAR with FA data, it has not been widely implemented, hence, its performance is still an open question.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Litmanen et al [54, this issue] provides some guidance on this, with an initial critical comparison of the two classes of methods. These authors found that while all methods mostly performed well, QFASA was favoured in the scenarios they evaluated, in part because it had significantly shorter computation times and less ambiguity in the results [54]. The value in combining data from bulk stable isotope values and fatty acids in mixing model analyses has long been recognized, and modelling approaches that can incorporate both types of data are now available [49,55].…”
Section: (F ) Diet Modelsmentioning
confidence: 99%